Neglect of Presence of Bacteria Leads to Inaccurate Growth Parameters of the Oligotrich Ciliate Strombidium sp. During Grazing Experiments on Nanoflagellates - Chen, Wan-Lin; Chiang, Kuo-Ping; Tsai, Sheng-Fang (Frontiers in Marine Science, 2020)
Oligotrich ciliates play a key role in linking microbial food webs to the traditional grazing food chain. Hence, the numerical (growth) and functional (grazing) responses of oligotrich ciliates are very important issues in studies of marine ecosystems. Most oligotrich ciliates feed mainly on nanoflagellates, while some of them also have the ability to consume bacteria. Up until now, studies of ciliates grazing on algae have not specifically excluded the effects of bacteria. In the present study, we found that the presence of bacteria in the algal culture medium affected the growth and grazing rates of ciliates grazing on nanoflagellates, resulting in an overestimate of gross growth efficiency at low relative algal concentrations. Strombidium sp. is prey selective mainly grazing on bacteria at low relative algal concentrations, but on algae at high relative algal concentrations. Carbon obtained from ciliate grazing on bacteria should be taken into account in the coastal zone surveys and especially in culture experiments to avoid unreasonable results of carbon flow.